Mother-daughter murder night eaudiobook A novel. - Simon, Nina (HarperAudio, 2023)
NEW YORK TIMES BESTSELLER - REESE'S BOOK CLUB PICK Nothing brings a family together like a murder next door. "I just loved how intriguing the mystery is but also the dynamics between a grandmother, a mother, and a teenage daughter."" —Reese Witherspoon Think: Gilmore Girls, but with murder. High-powered businesswoman Lana Rubicon has a lot to be proud of: her keen intelligence, impeccable taste, and the L.A. real estate empire she's built. But when she finds herself trapped 300 miles north of the city, convalescing in a sleepy coastal town with her adult daughter Beth and teenage granddaughter Jack, Lana is stuck counting otters instead of square footage—and hoping that boredom won't kill her before the cancer does. Then Jack—tiny in stature but fiercely independent—happens upon a dead body while kayaking. She quickly becomes a suspect in the homicide investigation, and the Rubicon women are thrown into chaos. Beth thinks Lana should focus on recovery, but Lana has a better idea. She'll pull on her wig, find the true murderer, protect her family, and prove she still has power. With Jack and Beth's help, Lana uncovers a web of lies, family vendettas, and land disputes lurking beneath the surface of a community populated by folksy conservationists and wealthy ranchers. But as their amateur snooping advances into ever-more dangerous territory, the headstrong Rubicon women must learn to do the one thing they've always resisted: depend on each other.